2022
DOI: 10.3389/fonc.2022.923260
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges of targeting c-Met in the treatment of digestive tumors

Abstract: At present, a large number of studies have demonstrated that c-Met generally exerts a crucial function of promoting tumor cells proliferation and differentiation in digestive system tumors. c-Met also mediates tumor progression and drug resistance by signaling interactions with other oncogenic molecules and then activating downstream pathways. Therefore, c-Met is a promising target for the treatment of digestive system tumors. Many anti-tumor therapies targeting c-Met (tyrosine kinase inhibitors, monoclonal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 139 publications
0
10
0
Order By: Relevance
“…We hypothesized that GJB4 activates the MET signaling pathway, then induces cell cycle progression and upregulates metastatic properties in pancreatic cancer cells. AKT, which is recognized as a downstream target molecule of MET, is a positive regulator of the cell cycle, and of migration/invasion 15,24 . Additionally, Src has been identified to be involved in the MET signaling pathway in lung adenocarcinoma 10 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that GJB4 activates the MET signaling pathway, then induces cell cycle progression and upregulates metastatic properties in pancreatic cancer cells. AKT, which is recognized as a downstream target molecule of MET, is a positive regulator of the cell cycle, and of migration/invasion 15,24 . Additionally, Src has been identified to be involved in the MET signaling pathway in lung adenocarcinoma 10 .…”
Section: Resultsmentioning
confidence: 99%
“…Except for mutated GJB4, which has been identified as the causative gene for erythrokeratodermia variabilis et progressiva, the roles and signaling pathways of GJB4 have not been completely As reported here, MET has emerged as a therapeutic target for patients with pancreatic cancer. 15 Selective MET inhibitors, such as tepotinib and capmatinib that are successful as cancer therapeutics, have been approved for patients harboring a MET exon 14 skipping mutation in non-small-cell lung cancer. 25,26 Regarding pancreatic cancer, Li et al found that MET is a bona fide pancreatic cancerspecific receptor tyrosine kinase through comprehensive analyses and that high MET expression is related to a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C-Met interacts with other oncogenic molecules (such as EGFR and RON) to activate downstream pathways, thereby mediating tumor progression and drug resistance ( 69 ). Similarly, there is also signal interaction between c-Met and VEGF and RON molecules in urologic neoplasms ( 40 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first to demonstrate the efficacy of combining c-Met inhibition with ionizing radiation in the treatment of hormone-independent PCa. In addition, c-Met was found to be abnormally activated in the absence of HGF in many solid tumors (69). Y. Dai et al (63) studied the reaction of PC-3 cells against HGF neutralizing antibody or small molecule c-Met kinase inhibitor (BMS-777607).…”
Section: Preclinical Studies Of C-met Targeting Therapy In Urologic N...mentioning
confidence: 99%